Record Of Tripartiella Bulbosa (Davis 1947) From The Fingerlings Of Labeo Rohita (Hamilton 1822) In Murshidabad, West Bengal With Comments On Prevalence Rate And Seasonal Incidence - Guhathakurta, Himadri (International Journal of Psychosocial Rehabilitation, 2020)
Protozoan ectoparasites pose a significant threat to the health and survival of fish populations, particularly during their vulnerable early life stages. In this study, an intensive icthyoparasitological survey was conducted in Murshidabad, India, with the aim of investigating the presence and prevalence of trichodinid ciliophorans, specifically Tripartiella bulbosa (Davis 1947), on fingerlings of Labeo rohita (Hamilton 1822). Fingerlings of Labeo rohita were sampled from multiple sites within Murshidabad district of West Bengal. The gills of the fingerlings were carefully examined, and the presence of Tripartiella bulbosa was recorded. The overall prevalence rate of Tripartiella bulbosa infestation was found to be 65.67%. Notably, the highest prevalence of infestation was observed during the winter season during a study in the year 2018, indicating a seasonal pattern of occurrence for this ciliate ectoparasite. The findings of this study provide valuable insights into the prevalence and seasonal patterns of Tripartiella bulbosa infestation in Labeo rohita fingerlings in West Bengal. This information can serve as a basis for developing effective strategies for the prevention, control, and management of trichodinid ciliate ectoparasites in aquaculture systems. Further research is warranted to investigate the impact of these ectoparasites on fish health and to explore potential treatment and mitigation measures for their control.